Impact of air pollutants on pediatric admissions for Mycoplasma pneumonia: a cross-sectional study in Shanghai, China - Ning Chen; Jianwei Shi; Jiaoling Huang; Wenya Yu; Rui Liu; Li Gu; Rong Yang; Zhaohu Yu; Qian Liu; Yan Yang; Sainan Cui; Zhaoxin Wang (BMC, 2020)
Abstract Background Children are especially vulnerable to pneumonia and the effects of air pollution. However, little is known about the impacts of air pollutants on pediatric admissions for Mycoplasma pneumonia. This study was conducted to investigate the impacts of air pollutants on pediatric hospital admissions for Mycoplasma pneumonia in Shanghai, China. Methods A cross-sectional design was applied to explore the association between pediatric hospital admissions and levels of air pollutants (fine particulate matter, particulate matter, ozone, sulfur dioxide, nitrogen dioxide, and carbon monoxide). Data on hospital admissions for pneumonia and levels of ambient air pollutants were obtained for the period of 2015 to 2018. Associations between pediatric admissions for Mycoplasma pneumonia and ambient air pollutants were calculated using logistic regression and described by the odds ratio and relevant 95% confidence interval. The hysteresis effects of air pollutants from the day of hospital admission to the previous 7 days were evaluated in single-pollutant models and multi-pollutant models with adjustments for weather variables and seasonality. Lag 0 was defined as the day of hospital admission, lag 1 was defined as the day before hospital admission, and so forth. Results In the single-pollutant models (without adjustment for other pollutants), pediatric hospital admissions for pneumonia were positively associated with elevated concentrations of nitrogen dioxide and fine particulate matter. A 0.5% increase in daily admissions per 10-μg/m3 increase in the nitrogen dioxide level occurred at lag 1 and lag 2, and a 0.3% increase in daily admissions per 10-μg/m3 increase in fine particulate matter occurred at lag 1. In the multi-pollutant models, nitrogen dioxide and fine particulate matter remained significant after inclusion of particulate matter, ozone, sulfur dioxide, and carbon monoxide. Conclusions This study illustrated that higher levels of nitrogen dioxide and fine particulate matter increase the risk of pediatric hospitalization for Mycoplasma pneumonia in Shanghai, China. These findings imply that the high incidence of Mycoplasma pneumonia in children in Asia might be attributed to the high concentration of specific air pollutants in Asia.